The effect of modal localization on reverberant energy decay in a case of two acoustically coupled rooms - Meissner, Mirosław (Archives of Acoustics, 2006)
In the paper a modal analysis was used to describe a reverberation phenomenon in an irregularly shaped room. A theoretical model was limited to low sound frequencies, when eigenmodes are lightly damped, thus they may be approximated by normal acoustic modes of a hard-walled room. A utility of this method was demonstrated in a numerical example where the room in a form of two acoustically coupled rectangular subrooms was considered. A reverberation time was evaluated individually for each subroom from time decay of acoustic pressure amplitude for different distributions of absorbing materials of room walls and various positions of sound source under the condition that a total room absorption remained constant. Calculation results have shown a great influence of modes localization on a reverberant energy decay for a large difference between the absorption coefficients of walls in subrooms, because in this case for frequencies of some localized modes a substantial increase in the reverberation time was observed.